Criminal law today - Schmalleger, Frank (Pearson, 2017)
The nature and history of criminal law -- Criminal liability and the essence of crime -- Expanding the concept of crime -- Extending criminal liability : inchoate offenses and parties to crime -- Justifications as defenses -- Defenses : excuses and insanity -- Crimes against persons : homicide -- Crimes against persons : assault, sex offenses, and other crimes -- Property and computer crimes -- Offenses against public order and the administration of justice -- Offenses against public morality -- Terrorism and human trafficking -- Victims and the law -- Punishment and sentencing